Bi and Mono Static Radar Cross Section Computation for Various Target’s Materials - Mohammed Ahmed, Ahmed; H. Ali, Israa; Raheem Hatem, Haraa (International Journal of Engineering and Technology, 2018)
Radar cross section (RCS) is important parameter which gives an indication about the spatial waveform of the return signal from the target to the radar (Echo) which can be consider as a signature. RCS signature measurements for any physical objects like aircraft, tanks, and vessels is sophisticated processes and expensive, due to of using microwave instruments which should has the capability of illuminate the target with adequate energy, so that the radar can recognize the reflected signal from that object against the other objects in the floor which consider noise floor. In this paper, Computer Simulation Technology (CST) software is used to simulate the RCS for several targets material, and different angles. The target is modeled and simulated for different material and analysis of RCS is carried out with different angles using two systems. The first system is Monostatic and the second is bistatic with selected frequency for both is 9.4 GHz (X-band frequencies). The results of this work show that the target with steel material has a significant RCS for both bistatic and monostatic radar compared to the FR4 and wood materials; where FR4 is a composite material composed of woven fiberglass cloth with an epoxy resin binder that is flame resistant.Â Â Â